Projecting Reductions in Vehicle Kilometers Traveled from New Bicycle Facilities - Jamey Volker; Susan Handy (Findings)
This paper presents a simple method for projecting the impact of new bicycle facilities on vehicle kilometers traveled. Our method starts with existing short-duration bicycle counts on or near the facility corridor, then applies six adjustment factors to project reductions in vehicle kilometers traveled. We examine the feasibility of measuring each factor and the range of their potential values.